2020
DOI: 10.1080/21655979.2020.1717297
|View full text |Cite
|
Sign up to set email alerts
|

Targeting survivin sensitizes cervical cancer cells to radiation treatment

Abstract: Survivin is an inhibitor of apoptosis protein that functions to inhibit apoptosis, promote proliferation, and enhance invasion. It is selectively up-regulated in many human tumors and implicated in cellular radiation response through its role in apoptosis, cell division, and DNA damage response. This study aimed to investigate the effect and mechanisms of targeting survivin radiosensitivity in cervical cancer C33A cells. Here, the authors designed a small interfering RNA (siRNA) or plasmid-based small hairpin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…It has been shown that the long noncoding RNA (lncRNA) nR2F1-AS1 stimulates the malignant phenotype of osteosarcoma cells [ 28 ]. Inhibition of BIRC5 improves cervical cancer cell sensitivity to radiotherapy [ 29 ]. Nine genes, including BIRC5, may be biomarkers for HCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the long noncoding RNA (lncRNA) nR2F1-AS1 stimulates the malignant phenotype of osteosarcoma cells [ 28 ]. Inhibition of BIRC5 improves cervical cancer cell sensitivity to radiotherapy [ 29 ]. Nine genes, including BIRC5, may be biomarkers for HCC [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is located in distinct parts of the mitotic apparatus and plays an essential role in cell division and inhibition of apoptosis. Survivin is expressed in most human cancers, but not in normal adult tissues [19,20]. Inhibition of Survivin has been well-studied as a cancer therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the long non-coding RNA (lncRNA) nR2F1-AS1 promotes the malignant phenotype of osteosarcoma cells through the miR-485-5p/miR-218-5p/BIRC5 axis 26 . Inhibition of BIRC5 improves cervical cancer cells sensitivity to radiotherapy 27 . Nine genes, including BIRC5, may be biomarkers for HCC 28 .…”
Section: Discussionmentioning
confidence: 99%